Perspektıf Glokal Dalam Implementası Teachıng At The Rıght Level(Tarl) Pada Pembelajaran Berdıfrensıası Pada Kurıkulum Merdeka - Duhwi Indartiningsih; Neni Mariana; Heru Subrata (Elementary Teacher Education Program, Majalengka University, 2023)
Differentiated Learning in the Merdeka Curriculum is a combination of global and local, namely the philosophy of Ki Hajar Dewantara. Differentiated learning is implemented in Indonesia according to the TaRL approach and combines with the philosophy of Ki Hajar Dewantara as a global perspective in the locality in Indonesia. The differentiation of TaRL implementation in Indonesia is that it is adjusted to Ki Hajar Dewantara's philosophy, which is used for all subjects and not only for literacy and numeracy. The author believes that the Teaching at the Right Level (TaRL) approach can be used for all subjects and for elementary, junior high, and high school levels. This has been done in Indonesia that the Teaching at the Right Level (TaRL) approach in the Merdeka Curriculum, namely differentiated learning, can be used for all subjects for elementary, junior high and high school levels and is able to improve student learning outcomes and foster optimism in students learning according to their level making students more confident, comfortable and happy to learn in class. The author recommends that teachers develop and implement learning with the TaRL approach or differentiated learning for all subjects. Teachers can collaborate the TaRL approach with learning approaches or models that can optimise student learning outcomes